MyD88-mediated signaling prevents development of adenocarcinomas of the colon: role of interleukin 18 - Salcedo, Rosalba (The Rockefeller University Press, 2010)
Signaling through the adaptor protein myeloid differentiation factor 88 (MyD88) promotes carcinogenesis in several cancer models. In contrast, MyD88 signaling has a protective role in the development of azoxymethane (AOM)/dextran sodium sulfate (DSS) colitis-associated cancer (CAC). The inability of Myd88(−/−) mice to heal ulcers generated upon injury creates an altered inflammatory environment that induces early alterations in expression of genes encoding proinflammatory factors, as well as pathways regulating cell proliferation, apoptosis, and DNA repair, resulting in a dramatic increase in adenoma formation and progression to infiltrating adenocarcinomas with frequent clonal mutations in the β-catenin gene. Others have reported that toll-like receptor (Tlr) 4–deficient mice have a similar susceptibility to colitis to Myd88-deficient mice but, unlike the latter, are resistant to CAC. We have observed that mice deficient for Tlr2 or Il1r do not show a differential susceptibility to colitis or CAC. However, upon AOM/DSS treatment Il18(−/−) and Il18r1(−/−) mice were more susceptible to colitis and polyp formation than wild-type mice, suggesting that the phenotype of Myd88(−/−) mice is, in part, a result of their inability to signal through the IL-18 receptor. This study revealed a previously unknown level of complexity surrounding MyD88 activities downstream of different receptors that impact tissue homeostasis and carcinogenesis.